The Impact of Partial Solar Eclipse on the Observation of Neutral Hydrogen Emission Line - Jallod, Uday E.; Mahdi, Hareth S.; Ali, Lana T.; Abood, Kamal M. (Iraqi Journal of Science, 2024)
The research involves examining the influence of partial solar eclipse on the strength of neutral hydrogen from the Sun. Baghdad University Radio Telescope (BURT) was used to monitor the partial solar eclipse on the 25th of October, 2022. Radio observations from the Sun were recorded from 11:30 AM to 03:36 PM. This means that the HI emission from the Sun was recorded before, during and after the event. It was noticed, that at the moment of maximum eclipse, 46% of the Sun’s disk was covered by the Moon. For the purpose of this research, the solar radio wave intensity was monitored and the solar flux density was determined at different times, i.e. before, during and after the partial solar eclipse. The obtained results showed that both of the solar flux and power spectrum decrease with the progress of the eclipse until the moment of maximum eclipse, i.e. the moment at which the minimum values of solar flux density and antenna temperature were recorded (7 × 104 Jy and 80 K). Then, at the last moments of the partial eclipse, it was noticed that both parameters started to increase again due to the decrease in the area of the Sun’s disk until both reached their normal values. In Conclusion, the partial solar eclipse affects the strength of neutral hydrogen from the Sun because the Moon blocks the neutral hydrogen from the Sun during the solar eclipse.